Brain levels of nonapeptides in four labrid fish species with different levels of mutualistic behavior - Kulczykowska, Ewa (2016)
There is strong evidence that brain nonapeptides are implicated as modulators of a wide array of social and reproductive behaviors in fishes. However, the question remains, as to whether there is a link between the distribution of active nonapeptides across brain regions and fishes specific behavioral phenotypes. To explore this link we compared the nonapeptides' profile across the brains of fishes representing different degrees of mutualistic behavior (here: cleaning behavior). Herein we studied the quantitative distribution of both nonapeptides, arginine vasotocin (AVT) and isotocin (IT), in the brains of four species of fish belonging to the family Labridae: two are obligatory cleaners throughout their entire life (Labroides dimidiatus and Labroides bicolor), one species is a facultative cleaner (Labropsis australis; juveniles are cleaners and adults are corallivorous), and one is a non-cleaner species, corallivorous throughout its entire life (Labrichthys unilineatus). The biologically available AVT and IT concentrations were measured simultaneously in distinct brain macro-areas: forebrain, optic tectum, cerebellum and brain stem, using liquid chromatography-tandem mass spectrometry (LC-MS/MS). We showed that the levels of both AVT and IT varied significantly across species, as measured in the whole brain or in the specific macro-areas. Significantly higher AVT concentrations in the cerebellum which were found in the obligate cleaners seemed to be related to expression of mutualistic behavior. On the other hand, the higher levels of brain IT in the non-cleaner L. unilineatus suggested that these might be linked to the development of sexual dimorphism, which occurs only in this non-cleaner species.